Analisis Ketidakpatuhan Belarus Kepada Council of Europe Convention on Action Against Trafficking in Human Beings - Annisa Nur Adillia (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The issue of human trafficking remains a major concern for countries worldwide, including Belarus. Belarus has made various efforts to address this issue, including ratifying the Council of Europe Convention on Action Against Trafficking in Human Beings in 2013. Despite being the first non-member state to ratify the convention, findings by GRETA, the convention's monitoring body, indicate a violation by Belarus of the convention's rules. This article aims to analyze the factors of non-compliance by the Belarusian government with the Council of Europe Convention on Action Against Trafficking in Human Beings using Chayes & Chayes' Compliance Theory. Based on the analysis of Chayes & Chayes' non-compliance factors, Belarus' violation of the convention is due to the ineffectiveness of the legislative system and authority, based on the ambiguity of the convention's rules, and the country's limited capabilities in providing experts and addressing the vulnerability of the Roma community.
Entry oleh Arif 2026 Maret 05
Keywords: Human Trafficking; Belarus; International Regime; Compliance Theory